Randomized, double-masked clinical trial evaluating corneal endothelial cell loss after cataract extraction and intraocular lens implantation: Fluid-based system versus ultrasound phacoemulsification - Sandoval, Helga P; de Castro, Luis E Fernández; Vroman, David T; Solomon, Kerry D (Cornea, 2006)
To assess the endothelial cell loss after cataract extraction using a fluid-based system and compare it with conventional ultrasound. A total of 46 eyes of 23 patients with up to 3+ bilateral cataract were included. The first eye was randomized to either fluid-based system or conventional ultrasound, and the fellow eye received the alternate system. Visual acuity and ultrasound pachymetry were measured preoperatively and at 1 day, 1 week, and 1 and 3 months postoperatively. Specular microscopy was performed preoperatively and 3 months after the surgery. Data was analyzed using the paired t test and Wilcoxon signed rank test. A P value less than 0.05 was considered statistically significant. Postoperatively, no significant differences were found among the groups. However, there was a significant difference (P < 0.01, analysis of variance with Tukey as posttest) in corneal pachymetry at day 1 after the surgery compared with baseline in both groups. There was a 6.3% and 7.9% loss of endothelial cells in the fluid-based system and ultrasound group, respectively. Visual acuity, pachymetry, and endothelial cell loss after cataract extraction and intraocular lens implantation using a fluid-based system is similar to conventional ultrasound.